Um estudo das regras de uso do hífen, segundo o acordo ortográfico de 1990 - Antunes, Ciro Carlos (2014)
This paper deals with the use of the hyphen in the word formation, as the Portuguese Spelling Agreement, made between 1986-1990 and approved by the nations that make up the Community of Portuguese Language Countries. Justifies the investigation because , although the Orthographic Agreement tax from 1996 presents a set of rules for the use of the hyphen in the word formation, there are many exceptions to every rule, causing difficulties. The problem is to answer the following questions: 1) Why use the hyphen in the word formation? 2) When the use of the hyphen is needed? 3) If Portuguese is a language accent, ie, intensity, native speakers recognize prefixes and suffixes accented and inacentuados? 4) In the derived and compound forms, the place selected for the accent in lexemes, entails the use of the hyphen? 5) Why multiple prefixes in Portuguese are accentuated if the affixes are treated by traditional grammarians as dependent ways that can not occur by itself in utterances? This work has the objective to contribute to a reflection on the Orthographic Agreement of 1990 and the formation of words Morphology part of our normative grammars of standard use. The specific objectives : 1) to present a brief history of English spelling and its orthographic reforms , to situate the distance between Brazil and Portugal , 2) present difficulties on the Morphology for word formation in our grammars in grammatical usage pattern , 3) examine the rules of use of the hyphen in derived words , and 4) examine the rules of use of the hyphen in compound words . The methodological approach was theoretical and analytical to a corpus consists of examples given in the 1990 Agreement in Brazilian spelling and grammar guides. The results indicate that, for the use of the hyphen: 1. The rules of the hyphen in the word formation derived by prefixing and suffixing were built with oscillation criteria: a) semantic b) morphological c) syntactic d) phonetic e) spelling f) morphosyntatic g) morfofonético. 2. Varying criteria create difficulties for the use of the hyphen and the same are present in the grammar item: Word formation. It follows the need to review the item related to the formation of words, which is spongy and confused, in Brazilian traditional grammar. Without this revision of any rule for hyphenation, word formation, it is difficult to elaborate